Urban wastewater treatment plants as hotspots for antibiotic resistant bacteria and genes spread into the environment: a review - Rizzo, L. (2014)
Urban wastewater treatment plants (UWTPs) are among the main sources of antibiotics' release into the environment. The occurrence of antibiotics may promote the selection of antibiotic resistance genes (ARGs) and antibiotic resistant bacteria (ARB), which shade health risks to humans and animals. In this paper the fate of ARB and ARGs in UWTP's, focusing on different processes/technologies (i.e., biological processes, advanced treatment technologies and disinfection), was critically reviewed. The mechanisms by which biological processes influence the development/selection of ARB and ARGs transfer are still poorly understood. Advanced treatment technologies and disinfection process are regarded as a major tool to control the spread of ARB into the environment. In spite of intense efforts made over the last years to bring solutions to control antibiotic resistance spread in the environment, there are still important gaps to fill in. In particular, it is important to: (i) improve risk assessment studies in order to allow accurate estimates about the maximal abundance of ARB in UWTPs effluents that would not pose risks for human and environmental health; (ii) understand the factors and mechanisms that drive antibiotic resistance maintenance and selection in wastewater habitats. The final objective is to implement wastewater treatment technologies capable of assuring the production of UWTPs effluents with an acceptable level of ARB.